ASUHAN KEPERAWATAN PADA PASIEN DIABETES MELITUS TIPE II DENGAN PEMBERIAN INTERVENSI MANAJEMEN HIPOGLIKEMIA DI RUANG IGD RSUD KOTA TANGERANG - Meynur Rohmah; Zahrah Maulidia Septimar; Djati Aji Nurbiantoro; Afrina Kusuma Dewi; Ati Setiawati; Tsani Dermawan; Yeni Gumiati; Dwi Sagita Apriyani; Ibnu Rizal Syarifudin (Nusantara Hasana Journal, 2023)
Diabetes is a metabolic disorder characterized by abnormalities in carbohydrate, fat and protein metabolism caused by decreased insulin secretion or decreased insulin sensitivity which causes chronic complications. Based on the results of health data in Tangerang City as one of the Provinces of Banten which has the highest prevalence of Diabetes Mellitus from other Regencies/Cities of 1.7% based on (Rikesdas 2013). The making of this paper is to find out how nursing care is for patients with type II DM. Nursing diagnoses that emerged in this case included unstable blood glucose levels, impaired gas exchange, and risk of electrolyte imbalance. Where the interventions carried out included hypoglycemia management, airway management, respiratory monitoring, inhalation drug therapy, and hypokalemia electrolyte management. The way to collect data on patients is by conducting interviews with patients and conducting primary and secondary assessments on patients. The results of the implementation include increased blood sugar, increased level of consciousness, decreased dyspnea, improved respiratory rate and oxygen saturation, electrolyte balance is expected to increase after 1x administration of KCl correction. From the results obtained 3 nursing diagnoses, 3 nursing outcomes, 3 nursing interventions.